Pokusa scjentyzmu w sporze o ewolucję i inteligentny projekt? Ocena tezy Erkkiego Kojonena = The temptation of scientism in the debate on evolution and intelligent design? An evaluation of Erkki Kojonen`s thesis - Sagan, Dariusz (1979- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In his book "The Intelligent Design Debate and the Temptation of Scientism", Erkki Kojonen argues that in the debate on evolution and intelligent design, there is a tendency to attach greater value to scientific claims than to philosophical or theological considerations, i.e., a preference for scientism.
Keywords: teoria ewolucji; teoria inteligentnego projektu; teistyczny ewolucjonizm; naturalizm metodologiczny; neutralizm metodologiczny; theory of evolution; intelligent design theory; theistic evolutionism; methodological naturalism; methodological neutralism